2017
DOI: 10.5152/jarem.2016.1037
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Risk of Childhood Obesity in the Bağcılar region of İstanbul

Abstract: Objective: Childhood obesity has recently become a common health problem worldwide. In the struggle against obesity, studies have focused on the risk factors playing a role in the development of obesity. In this study, we assessed the risk factors playing a role in childhood obesity and the resulting obesity in the İstanbul Bağcılar Region. Methods:In total, 250 obese children, aged 4-15 years, and 98 non-obese children of the same age were included in this study. A standardized questionnaire aimed at determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…They showed that enuresis is more common in obese children than in normal weight control subjects. The probable explanations for this are common comorbidities in these patients, such as obstructive sleep apnea and type 2 diabetes mellitus (18). Obese children may have a slightly underestimated enuresis, and it warrants close attention to prevent unnecessary psychological distress in these children.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that enuresis is more common in obese children than in normal weight control subjects. The probable explanations for this are common comorbidities in these patients, such as obstructive sleep apnea and type 2 diabetes mellitus (18). Obese children may have a slightly underestimated enuresis, and it warrants close attention to prevent unnecessary psychological distress in these children.…”
Section: Discussionmentioning
confidence: 99%